Time-resolved detection of the CF3 photofragment using chirped QCL radiation. - Hancock, G; Horrocks, S; Ritchie, G; Helden, J; Walker, R (2008)
This paper demonstrates how a quantum cascade laser (QCL) in its intrapulse mode can provide a simple method for probing the products of a photolysis event. The system studied is the 266 nm photodissociation of CF3I with the CF3 fragments subsequently detected using radiation at approximately 1253 cm(-1) generated by a pulsed QCL. The tuning range provided by the frequency down-chirp of the QCL operated in its intrapulse mode allows a approximately 1 cm(-1) segment of the CF3 nu3 band to be measured following each photolysis laser pulse. Identification of features within this spectral region allows the CF3 ( v = 0) number density to be calculated as a function of pump-probe delay, and consequently the processes which populate and deplete this quantum state may be examined. Rate constants for the population cascade from higher vibrational levels into the v = 0 state, k 1, and for the recombination of the CF3 radicals to form C2F6, k2, are measured. The returned values of k1 = (2.3 +/- 0.34) x 10(-12) cm(3) molecule(-1) s(-1) and k2 = (3.9 +/- 0.34) x 10(-12) cm(3) molecule(-1) s(-1) are found to be in good agreement with reported literature values.